PERBAIKAN FAKTOR DAYA DENGAN PENAMBAHAN NILAI KAPASITOR SEBAGAI PENGHEMAT ENERGI LISTRIK PADA BEBAN LAMPU FLUORESEN - Suyanto, Muhammad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
The use of electrical energy is made as efficient as possible, therefore to get the economical value, especially in the use of Fluorescent lamps, it is necessary to make an effort how to use energy that approach the installed value. The effort was dane by in cir-cuit tests using fluorescent lamps with different capacitor values and comparing them with economical lamps. Having obtained the capacitor values, the experiment were carried out to collect the actual data of the installed power. The resuls of the experiments were analyzed and showed that the increasing values of capasitors were followed by better power factors so they approached the associated installed powers.